Factors Affecting Dental Caries of Preschool Children in Shiraz, 2014 - Soheila Shaghaghian; Masoud Abolvardi; Marzieh Akhlaghian (Shiraz University of Medical Sciences, 2018)
Statement of the Problem: Dental caries, the most common infectious disease, can lead to several consequences, including inflammation and bleeding of the gum, abscess formation, tooth loss, and subsequently loss of available space in the arch. Purpose: This study was designed to determine dental caries status of Shiraz preschool children and its related factors. Materials and Method: This cross-sectional study was conducted on the children registered in Shiraz kindergartens in 2014. The study recruited 453 children by randomized cluster sampling. We evaluated the children's demographic and oral hygiene factors, and their dental caries status using decayed, missed, and filled tooth (dmft) index and prevalence of the children with untreated dental caries. Relationship between the children's characteristics and their dental caries status was evaluated. Results: Only 119 children (30.1%) were caries-free. The children's mean dmft index was 3.88(±3.9). After controlling the effect of confounding factors, the children's dental caries status was significantly associated with variables indicating their socioeconomic status such as fathers' job, mothers' education, and number of children in the family. Furthermore, there was a significant association between the children's dental caries status and their oral hygiene habits such as frequency of tooth brushing. Conclusion: The dental caries status of the studied preschool children was not desirable which could be indicative of the inadequacy of the current preventive programs. To improve this issue, interventional preventive programs such as tooth brushing are recommended. The programs are more necessary for the children of low socioeconomic families and those with poor oral hygiene habits.